2016
DOI: 10.4103/0366-6999.178958
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Vestibular Testing on Distinguishing the Nerve of Origin for Vestibular Schwannoma and Predicting the Preservation of Hearing

Abstract: Background:Determining the nerve of origin for vestibular schwannoma (VS), as a method for predicting hearing prognosis, has not been systematically considered. The vestibular test can be used to investigate the function of the superior vestibular nerve (SVN) and the inferior vestibular nerve (IVN). This study aimed to preoperatively distinguish the nerve of origin for VS patients using the vestibular test, and determine if this correlated with hearing preservation.Methods:A total of 106 patients with unilater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…He et al, using cVEMPs and caloric test abnormalities, found the nerve source of the tumor could be predicted in only 22 of 68 patients, as the majority had abnormalities on both tests. 97 Similarly, both Suzuki et al and Ushio et al found similar rates of cVEMP abnormalities for schwannoma originating from either nerve division. 98,99 Despite most schwannoma originating from the vestibular nerve, secondary changes in the labyrinth are known to occur.…”
Section: Vestibular Neuritismentioning
confidence: 76%
See 1 more Smart Citation
“…He et al, using cVEMPs and caloric test abnormalities, found the nerve source of the tumor could be predicted in only 22 of 68 patients, as the majority had abnormalities on both tests. 97 Similarly, both Suzuki et al and Ushio et al found similar rates of cVEMP abnormalities for schwannoma originating from either nerve division. 98,99 Despite most schwannoma originating from the vestibular nerve, secondary changes in the labyrinth are known to occur.…”
Section: Vestibular Neuritismentioning
confidence: 76%
“…This would be an advantage clinically since hearing preservation is often better for schwannoma arising from the superior nerve. 96,97 Unfortunately, studies do not support this. He et al, using cVEMPs and caloric test abnormalities, found the nerve source of the tumor could be predicted in only 22 of 68 patients, as the majority had abnormalities on both tests.…”
Section: Vestibular Neuritismentioning
confidence: 99%
“…Previous studies established a possibility for prediction of the prognosis of hearing preservation surgery in VSs [18][19][20] . Also, there are studies on intraoperative findings of tumor origin, SVN(superior vestibular nerve), and IVN (inferior vestibular nerve), and concludes SVN originating tumors is associated with better hearing preservation 19,20,24 . Preoperative determination of tumor origin (SVN or IVN) has some controversies; a study by Ushio et al demonstrates no significant correlation of localizing tumor origin 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative determination of tumor origin (SVN or IVN) has some controversies; a study by Ushio et al demonstrates no significant correlation of localizing tumor origin 25 . On the other hand, other papers show the usefulness of caloric and vestibular-evoked myogenic potential(VEMP) for determining tumor origin 24,26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation